Modelling archers` scores at different distances to quantify score loss due to equipment selection and technique errors - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
Archers lose score through parameters that vary either linearly or quadratically with distance to the target. An archer`s arrow group on the target can be modelled using a normal distribution with the standard deviation depending upon the archer`s skill level and the distance to the target. Structuring the standard deviation to include both a component that varies linearly with distance and another that varies quadratically with distance provides a mechanism to quantify the impact on the archer`s score of various technique and equipment errors. In this article, the impact of wind drift and variable lateral bow angle (bow cant) have been quantified using the archer`s scores at target distances of 70 and 50 m, together with simulation using a Monte Carlo technique.